Australasian Conference on Information Systems 2018 2018
DOI: 10.5130/acis2018.dj
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Boundary Conditions of Social Influence for Social Media Research

Abstract: Along with the proliferation of social networking sites (SNS), people around the world have gained the ability to influence each other in terms of many aspects of lives may it be a political interest or a simple purchase decision. However, most of the SNS studies have employed social influence constructs that were established prior to the advent of SNS to understand the nature and impact of social influence. Even though the application of such theories for SNS has generated a wealth of knowledge, it is vital t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Therefore, Media interactions strongly influence the evaluation of products, services, and interactive trends, which enhance the customer's experience with the website, which contributes to building brand loyalty through the interaction and telling experiences with users. This finding is consistent with the study of Chandrasekara and Sedera (2018), which found the positive impact of social media marketing on social interaction, which in turn affects the branding and buying intentions of website users, as 70% of consumers visit social media to obtain product information brands and 49% of consumers make their purchasing decisions based on the information obtained.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, Media interactions strongly influence the evaluation of products, services, and interactive trends, which enhance the customer's experience with the website, which contributes to building brand loyalty through the interaction and telling experiences with users. This finding is consistent with the study of Chandrasekara and Sedera (2018), which found the positive impact of social media marketing on social interaction, which in turn affects the branding and buying intentions of website users, as 70% of consumers visit social media to obtain product information brands and 49% of consumers make their purchasing decisions based on the information obtained.…”
Section: Discussionsupporting
confidence: 91%